The South Africa-Zimbabwe remittance corridor: an analysis of its characteristics and the cost of remittance payments - Onyango, Beryl Morine Achieng' (Department of Finance and Tax, 2022)
Zimbabwean migrants in South Africa often send financial support to their relatives in Zimbabwe. This financial support is known as remittances and is sent as cash or in-kind. This study investigated the characteristics of the South African-Zimbabwe remittance corridor. A critical investigation of the remittance channels used, the type of remittances sent, and the remittance transaction costs involved was done. Data for use in this study was collected through interviews with remittance service providers and by actual remittance transfers to Zimbabwe. A qualitative and quantitative analysis of data using statistical analysis techniques was done. From the analyzed data, it was observed that remittance service providers fall into two channels: formal and informal. The informal remittance channels were found to be the most popular in this corridor. The popularity of informal channels can be attributed to lower transaction costs and a lack of documentation needed from the sender. Informal remittance channels do not require the remittance sender to provide any identification document, therefore, undocumented Zimbabwean migrants opt for them. Long-distance buses that serve the South Africa-Zimbabwe route were found to be a popular channel of sending remittances - both cash and in-kind - to Zimbabwe. In-kind remittances have gained popularity due to the perennial lack of household consumer goods in Zimbabwe. Due to the national lockdown imposed in South Africa as a response to the Covid19 global pandemic, the study was unable to find the volume of remittances that is sent through the informal longdistance buses and trucks. The lockdown resulted in the closure of borders and non-essential travel was not permitted. The study found that the remittance transaction cost in the South AfricaZimbabwe corridor was higher than the global average cost of 6.84% (for formal channels) and the United Nations Sustainable Development Goal of 3% by the year 2030.